2016
DOI: 10.1097/ta.0000000000001250
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on failure-to-rescue in geriatric trauma patients

Abstract: Prognostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 22 publications
1
69
0
Order By: Relevance
“…43 Although failure to rescue depends on hospital characteristics relative to patient characteristics, recent studies of older surgical patients found higher rates of failure to rescue by patient characteristics relevant to an aging population, including frailty status and age. 16,[44][45][46][47][48] The mechanism of failure to rescue in frail patients is unclear and may relate to the definition of frailty, which is an inability to restore homeostasis following insults such as complications, or more subtle cultural influences such as reluctance to attempt rescue in frail surgical patients. 16,49 In our study, rates of failure to rescue did not vary by frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…43 Although failure to rescue depends on hospital characteristics relative to patient characteristics, recent studies of older surgical patients found higher rates of failure to rescue by patient characteristics relevant to an aging population, including frailty status and age. 16,[44][45][46][47][48] The mechanism of failure to rescue in frail patients is unclear and may relate to the definition of frailty, which is an inability to restore homeostasis following insults such as complications, or more subtle cultural influences such as reluctance to attempt rescue in frail surgical patients. 16,49 In our study, rates of failure to rescue did not vary by frailty status.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of falls increases with age, affecting 28%–35% of older people globally every year. 1 Falls are the most common cause of trauma and trauma-related deaths among older people, 2 and morbidity and mortality after a fall are correlated with frailty, 3 while age constitutes the strongest predictor of mortality. 4 In 40%–60% of cases, falls are associated with major lacerations, fractures, or traumatic brain injuries, 5 resulting in reduced physical activity, deconditioning, functional decline, impaired ability to perform daily activities, social isolation, reduced quality of life, depression, increased risk of subsequent falls, and institutionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and mortality seems correlated with frailty[15] and age constitutes the strongest, but not unique, predictor of mortality[16]. A recent systematic review identified six risk factors appearing in more than one study that could be used to predict falls in the geriatric population: Previous fall, living alone, walking aid, depression, cognitive deficit and use of > 6 medications[16].…”
Section: Mechanisms Of Injurymentioning
confidence: 99%
“…Given these limitations, the frailty index[15,44-46] can be of interest to predict which patients are at highest risk of having poor outcomes and then require focused interventions. Joseph et al[60] recently showed that frail patients were more likely to develop in-hospital complications (non-frail: 12%, pre-frail: 17.4%, and frail: 33.4%, P = 0.02) and an adverse discharge disposition.…”
Section: Can We Predict Outcome?mentioning
confidence: 99%